Polish witches, Slavic gods: emotional construction of nativeness in the narratives of Polish Wiccans - Malita-Król, Joanna (Journal of contemporary religion, 2025)
Slavic motifs seem to have entered mainstream culture in Poland in recent years. Similarly, the dominant Pagan religion in Poland—Rodzimowierstwo—is reviving the pre-Christian Slavic religion. This article aims to examine whether Polish Wiccans, adherents of an originally British religion, include Slavic gods and festivals in their rituals. The orthopraxic nature of Wicca as a religion enables the incorporation of local elements and numerous examples from around the world are presented to prove it. Although the unification of the Wiccan ritual framework and Slavic elements is technically feasible, it is argued that the actual application does not often occur in Poland. Furthermore, there is no clear trend towards creating a new Wiccan–Slavic tradition. Two reasons contribute to this situation: firstly, the aspect of knowledge (the sources of the pre-Christian Slavic religion are described as inadequate) and, secondly, the aspect of emotions and emotional construction of ‘us-ness’ and what is considered ‘ours’ (the participants in this study did not feel enough connection with what is generally understood as Slavdom). The following analysis is based on an open-ended questionnaire and in-depth interviews with Polish Wiccans and explores the significance of emotions and the self-identification of the research participants.